Tertiary Education in Vietnam: Responding to the New Normal - Huyen K. Pham; Anh Thi Phuong Le; Nguyen Thi Thao Ho (Tecno Scientifica Publisher, 2026)
The new normal created by COVID-19 has opened opportunities for higher education institutions (HEIs) worldwide to digitalize their teaching and learning management. In Vietnam, beyond the adoption of e-learning and distance learning, strategic-level actions have been implemented to ensure a cohesive online experience for students, supporting both academic and personal development. This study examines a private Vietnamese HEI’s response to the new normal using a case study approach, analyzing the quality of these actions through students’ satisfaction and feedback surveys. Although limited to the Vietnamese context, this study provides a valuable example of digitalizing learning and teaching management in tertiary education, illustrating how HEIs can overcome challenges posed by the new normal.